2001
DOI: 10.1159/000051725
|View full text |Cite
|
Sign up to set email alerts
|

Topical Metronidazole Does Not Abate UVB-Induced Erythema

Abstract: Background: The capacity of topical metronidazole to reduce erythema severity scores in rosacea has been attributed to its anti-inflammatory activity. Methods: Nine healthy subjects were irradiated on three 1-cm2 areas on their volar forearm with 2 MEDs of UVB. Twenty-four hours later, one of the irradiated areas was treated daily with metronidazole 1% vanishing cream, one with the vehicle only and the third was left untreated (control). The intensity of erythema was measured, at 24, 48, 72 and 96 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Compared to placebo, metronidazole 0.75% gel was found to have a significant effect on erythema within the second 15 days of treatment, on D. folliculorum between the forty-fifth and sixtieth days of treatment, although Guarrera et al [30]reported that topical metronidazole 1% vanishing cream did not have any effect on UVB-induced erythema. We suggest that topical metronidazole may reduce erythema severity scores in rosacea since it is also possible that UVA-mediated mechanisms may well contribute to erythema in rosacea; metronidazole has photoprotective effects, especially with regard to UVA.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to placebo, metronidazole 0.75% gel was found to have a significant effect on erythema within the second 15 days of treatment, on D. folliculorum between the forty-fifth and sixtieth days of treatment, although Guarrera et al [30]reported that topical metronidazole 1% vanishing cream did not have any effect on UVB-induced erythema. We suggest that topical metronidazole may reduce erythema severity scores in rosacea since it is also possible that UVA-mediated mechanisms may well contribute to erythema in rosacea; metronidazole has photoprotective effects, especially with regard to UVA.…”
Section: Discussionmentioning
confidence: 99%
“…Repetitive UVB irradiation of hairless mice has been used previously to evaluate test compounds on skin photoageing, photodamage, inflammation and tumor development . UVB–induced erythema also has been used clinically in healthy volunteers to assess the photoprotective and anti‐inflammatory activity of potential therapeutic agents . In the latter studies, UVB doses of approximately one to two times the minimal erythema dose were used, with erythema measured by chromameter.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24] UVB-induced erythema also has been used clinically in healthy volunteers to assess the photoprotective and anti-inflammatory activity of potential therapeutic agents. [25,26] In the latter studies, UVB doses of approximately one to two times the minimal erythema dose were used, with erythema measured by chromameter. In the present study, we determined experimental conditions under which brief exposure to UVB induces skin erythema without causing skin ulcerations or other obvious skin damage.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the terminology ‘acne rosacea’ seems appropriate. As far as therapeutic treatment is concerned, the anti-inflammatory activity is not the only way through which topical agents can reduce the clinical severity of rosacea [28]; eradication of ectoparasites has been reported to be effective in PPR rosacea [29]. …”
Section: Discussionmentioning
confidence: 99%